Konseling Sebaya Sebagai Metode untuk Meningkatkan Perilaku Prososial Siswa - Silvia Yula Wardani; Rischa Pramudia Trisnani (Universitas Ahmad Dahlan, 2015)
This study aims to determine the effectiveness of peer counseling to increase prosocial behavior of students of SMP Negeri 8 Madiun. The research design study is pre-experimental design. The research subject was eight students taken through purposive sampling techniques. Data collection instrument used a scale of prosocial behavior. The effectiveness of peer counseling test to increase prosocial behavior of students was analyzed using the Wilcoxon Match Pairs Test formula. The analysis of data shows that the students prosocial average score change was 61 or 36 % , from a pretest data average was 85 or 49 %, to 146 , or 85 % on average of the posttest data. The results showed that peer counseling is effective to increase prosocial behavior of students of SMP Negeri 8 Madiun. The results of this study can be used as reference material for the guidance and counseling teachers in the preparation of peer counseling program to develop students’ prosocial behavior.